KNOWLEDGE ANALYSIS OF THE PROSPECTIVE BRIDE ABOUT TETANUS TOXOID IMMUNIZATION IN WEDDING PREPARATION - Meda Yuliani; Dewi Nurlaela Sari; Antri Ariani; Susilawati Susilawati (Green Publisher, 2022)
Tetanus neonatorum is one reason, Dead baby. So an immunization program, tetanus toxoid for catin, woman age fertile and mother pregnant. Knowledge is one base formation attitude, then from that knowledge paint about Tetanus toxoid immunization is critical in the effort prevention happening infection to mother and baby as well as for push number of Dead baby a consequence infected tetanus disease. Type study this is a descriptive quantitative study. The population in the research is the whole candidate registered bride and groom wedding at the office district religious affairs cirupan, arrowroot, as many as 95 couples with amount sample A total of 76 teams using quota sampling. A tool used for data retrieval is a questionnaire. Analysis of the data used is distribution frequency. Research results show that more than half (57.8%) of respondents lack knowledge about Tetanus toxoid immunization. Researchers hope the KUA can weave cooperation with local service health to gift education about health reproduction on satin as supplies readiness reproduction, prepare life house healthy stairs, one of them gift education in the implementation of Tetanus toxoid immunization.